Resistance to doxorubicin correlated with dysregulation of microRNA-451 and P-glyoprotein, caspase 3, estrogen Receptor on Breast Cancer cell line - Indwiani Astuti; Torizal GF; Sa’adah N; Oktriani R; Wardana T; Ysrafil .; Teguh Aryandono; Sofia Mubarika (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Doxorubicin (Dox)has beenused widely in breast cancer therapy. One of the problems in chemotherapy is the development of resistance to chemotherapy that lead to metastasis and relapse aggressiveness of cancer. MicroRNAs (miRNAs) are small non-coding RNA that regulate protein expression and play role in carcinogenesis, as well as cancer chemotherapy resistance. MiR-451 is classified as tumour suppressor miRNA, that binds to messenger RNA (mRNA) of MDR1, and leads disruption of P-glycoprotein (Pgp) expression. Thestudy aimed to investigate the association between miR-451 and Pgp related with Dox resistance mechanism. In silico analysis was conducted to predict the binding affinity between miR-451 and mRNA of MDR1. The MCF-7 cell line was used as wild type model, while MCF-7/Dox was used as a model of resistance. qPCR was conducted to calculated miR-451 expression and immunocytochemistry was used to observe Pgp expression. miRNA was down-regulated in both on MCF-7 and MCF-7/Dox. On the other hand, Pgp expression was detectable in the cytoplasmic and cytoplasmic membrane in MCF-7/Dox. The Pgp expression was higher in the MCF-7/Dox compared to MCF-7. In conlusion, the over expression of Pgp is associated with the resistance to MCF-7/Dox.